The Relationship of Urban Adolescent Stressors to The Online Addiction of Game on Junior High School - Friendy Ahmidar; Alifiati Fitrikasari (The Avicenna Medical Journal, 2020)
Background: The presence of online games has brought great impact on personal development and adolescent adaptation. Urban adolescents are more vulnerable to the complexity and stress. Chronic exposure to social and environmental stress must be related to psychological pressure which can lead adolescent becoming online game addicts. The aim of this study was to determine the correlation between urban adolescent stress and online games addiction.Methods: This is an observational study with a crosssectional study design. Urban adolescent stress was measured using Urban Hassles Index whereas online game addiction was measured using Indonesia Online Game Addiction Questionnaire. This study used chi square as the statistic test.Results: This study included 280 students as research subjects, 112 subjects (40.0%) were online game addicts. Urban adolescent stress has a significant correlation with online games addiction (p = 0.019).Conclusion: There is a correlation between urban adolescent stress and online game addictions.